AKSELERASI MUTU PENDIDIKAN DASAR MELALUI TOTAL QUALITY MANAGEMENT - Abdul Rozak (Almarhalah, 2022)
AbstractThe low quality of human resources is a fundamental problem that hinders the economic development of the country. Statistical data shows that Indonesia's labor force is still dominated by people with basic education. This low level of education is an obstacle to our ability to produce competitive products using the latest technology. The method used in this study uses a literature method or approach. Literature research can be interpreted as a series of activities related to how data in the form of literature is collected, compiled, and analyzed to produce findings. The application of Total Quality Management (TQM) in the field of education must be fundamental and sustainable. Educational institutions should adopt TQM as a process and initiative to improve and restore the quality of education in managed school institutions, since the application of TQM principles produces good results in achieving quality. The principles of TQM are likened to pillars that strengthen and support the organizational movement of a school institution to achieve the specified quality.Keywords: Elementary School, Quality, Total Quality Management